ISOLASI DAN IDENTIFIKASI BAKTERI GENUS Sphingomonas DARI DAUN PADI (Oryza sativa) DI AREA PERSAWAHAN CIBINONG - Gabriela Christy Sabbathini; Sri Pujiyanto; w wijanarka (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
The unique ability of the genus Sphingomonas bacteria as degrade the contaminants refractory contaminants, to serve as the antagonists bacteria to phytopathogenic fungi, and capable to secrete hidhly useful exopolysaccharide gellan make these bacteria may play an important role in various industrial fields. Exploitation of the metabolic capabilities by genus Sphingomonas bacteria can provide significant commercial advantages for biotechnology.The species of Sphingomonas are often found associated with the rice plant as one of the endophytic bacteria that can be cultured. This study aims to isolate the local bacteria that can produce gellan gum from the leaves of the rice plant (Oryza sativa). The isolation process is done with a spread plate method suspension of rice leaves on Nutrient Dextrose Agar (NDA) media. Single colonies of bacteria that can be isolated then identified by colony PCR method to proceed at sequencing process. Sequencing followed by equalization sequences on the BLAST program shows four isolates of the genus Sphingomonas which isolates XA1, XA2, XA6, XA12 with the results are Sphingomonas sp. Fse41, Sphingomonas sp. Fse41, Sphingomonas sanguinis L4-317 strain and Sphingomonas sp. MLB01Keywords: endophytic bacteria, padi, Sphingomonas